New fluorescent heterocyclic materials: Synthesis, solvatochromic and fluorescence properties - Costa, Susana P. G. (2006)
Thienyl- and bithienyl-1,3-benzothiazoles 1 and 2 were synthesised by reacting various formyl thienyl and bithienyl derivatives with o-aminobenzenethiol in moderate to excellent yields. Evaluation of the solvatochromic and fluorescence properties of these compounds was carried out. Due to their strong fluorescence and also the strong push-pull character, benzothiazole derivatives 1 and 2 can be used as potential NLO materials or as fluorescent markers.